Assessment of consumers’ preference and willingness to pay for Boer cross goat Chevon in Nepal - Subedi, Sanjiv; Timsina, Krishna Prasad; Kadel, Raju (Nepal Agriculture Research Journal, 2025)
Domestic production of chevon does not yet meet the national demand. Efforts are being carried out since last decade to increase the goat production or so to introduce and adopt a high chevon yielding Boer goat in farming practices in Nepal.  Recent research findings have demonstrated that farming practices of Boer goat is well adoptable along with the marketing potentiality of Boer goat in Nepal. A total of 120 respondents selected randomly for the sensory analysis experiment and were interviewed. Two male goats, Boer cross (50% Boer blood) and Khari (100% local goat), of the same age were slaughtered. Shredded chevon from the goat’s shoulder after cooking was used for organoleptic taste. As per consumer’s response, Boer goat chevon was found to have higher tenderness and juiciness than Khari, while Khari was found to have a better flavor than Boer. Two thirds of the consumers preferred Boer goat chevon in terms of overall satisfaction compared to Khari. The rank-ordered logit regression revealed that tenderness has a positive and significant influence (p